Stem cell-derived exosome signature reveals immunoregulatory phenotype through downregulation of prostaglandin E synthase (PTGES) - Eyupoglu, H. O.; Eyupoglu, E.; Serakinci, N.; Tuzmen, S. (Wiley, 2023)
[Abstract Not Available]